The wise man and the prophet musa: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Wise Man and the Prophet Musa" recounts an encounter between the wise man and Prophet Moses (Musa). In the story, the wise man shares profound insights about faith, humility, and the nature of wisdom. The dialogue often explores the importance of recognizing divine guidance in life's trials. Through their interaction, the tale emphasizes the value of humility and the belief that true wisdom lies in understanding one's place in the greater scheme of creation.